Exploring the contribution of straw utilization to carbon emission reduction in Anhui Province (China) - Zhou Ye; Xiaohang Yu; Ruoyun Yao; Youzhi Yao (PLoS ONE, 2026)
Taking various prefecture-level cities in Anhui Province as the subject of this study, this research draws on data from the ‘Anhui Statistical Yearbook’ to analyze crop straw resources’ potential full utilization, and spatial distribution characteristics, in Anhui Province for the year 2023. The carbon neutralizing effect of straw full utilization was also evaluated using life cycle assessment. Results indicate that the total theoretical straw resources from major crops in Anhui Province in 2023 amounted to 5.213 × 10 7 tons (t), dominated by wheat, rice, and corn straw; which collectively accounted for 89.72% of the total. The carbon emission reductions from straw utilization through fertilization, animal feed, energy generation, substrate application, and raw material processing were approximately 4 × 10 6 , 1.07 × 10 6 , 5.8 × 10 5 , 9.8 × 10 4 , and 1.67 × 10 5 t of CO₂, respectively. Clarifying the total amount, types, potential utilization, and spatial distribution of straw resources at the city level is essential for promoting rational resource allocation and facilitating logicall regional planning for the utilization of those resources. These findings are of paramount importance towards efforts to achieve the goals of “Carbon peaking and carbon neutrality” (Dual-carbon) and fostering coordinated economic and social development in China. Under the framework of “dual carbon” national strategy and the overall layout of agricultural carbon emission reduction, the data analysis results of straw resource utilization in Anhui Province can serve as a reference for other regions to carry out relevant work.